Effect of Synbiotic and Postbiotic Supplements on Dental Caries and Periodontal Diseases—A Comprehensive Review - Twetman, Svante; Belstrøm, Daniel (International journal of environmental research and public health, 2025)
Caries and periodontitis affect a significant part of the global population. Regular oral hygiene, sugar restriction, and fluoride exposure are the main avenues for the maintenance of oral health, but the adjunctive use of prebiotics and probiotic bacteria has gained attention over the past decades. The microbial and clinical effects of these biological interventions have been thoroughly covered in systematic reviews. However, the combination of prebiotics and probiotics (synbiotics) may boost the clinical benefits, and postbiotics, being inanimate microorganisms, can, when added to oral hygiene products, offer a sustainable option. The aim of this narrative review was to summarize clinical trials on the adjunctive use of synbiotics and postbiotics in the prevention and management of dental caries, gingivitis, and periodontitis. We searched two databases (PubMed and Google Scholar) for relevant literature, and we identified 17 relevant papers, five on dental caries and 12 with periodontal endpoints. We found emerging evidence of low certainty that lozenges/tablets containing synbiotics or postbiotics could reduce caries incidence in preschool and schoolchildren in comparison with standard preventive care. The effect on adult patients with plaque-induced gingivitis was less consistent. For adults with periodontitis, the adjunctive use of synbiotic and postbiotic products seemed to enhance the outcome of conventional scaling and root planning. In conclusion, both dental caries and periodontitis are non-communicable diseases, closely associated with an unbalanced oral biofilm, and the application of microbial modulators, including synbiotics and postbiotics, display promising beneficial effects and warrant further research.